Consumer Data Protection Against Online Loan Debt Payments - Agung Suma Kurniawan; Levina Yustitianingtyas (Jurnal Justiciabelen, 2023)
In the era of digital economy innovation, people are trying to find new findings in the procurement of services for lending activities, which can be seen from the existence of money lending services on a digital basis which are considered to be able to build growth and the national economy. The type of observation used in this research is coherent research. Resolving disputes over payment of online loan debt and protecting consumer data is a complex problem in today's digital era. Consumers often become victims of the protection of their personal data by irresponsible online lenders. The sources of data used in this study are document laws, laws and regulations, and legal doctrines related to problem solving and consumer data protection. In using online loan services, consumers must provide a number of personal data, such as; name, address, telephone number, bank account number and other information. This can raise concerns for consumers regarding their security and privacy. To provide protection to consumers, data from the Indonesian fintech association (aftech), in 2019 there were around 15 million users of online loan services in Indonesia. In 2020 this number has increased by around 21 million users. In 2021 it is estimated that the number of users will increase again to 27 million. The results of this study indicate that consumer data protection and dispute resolution policies in Indonesia still need to be strengthened. bank account number and other data information. This can raise concerns for consumers regarding their security and privacy. To provide protection to consumers, data from the Indonesian fintech association (aftech), in 2019 there were around 15 million users of online loan services in Indonesia. In 2020 this number has increased by around 21 million users. In 2021 it is estimated that the number of users will increase again to 27 million. The results of this study indicate that consumer data protection and dispute resolution policies in Indonesia still need to be strengthened. bank account number and other data information. This can raise concerns for consumers regarding their security and privacy. To provide protection to consumers, data from the Indonesian fintech association (aftech), in 2019 there were around 15 million users of online loan services in Indonesia. In 2020 this number has increased by around 21 million users. In 2021 it is estimated that the number of users will increase again to 27 million. The results of this study indicate that consumer data protection and dispute resolution policies in Indonesia still need to be strengthened. in 2019 there were around 15 million users of online loan services in Indonesia. In 2020 this number has increased by around 21 million users. In 2021 it is estimated that the number of users will increase again to 27 million. The results of this study indicate that consumer data protection and dispute resolution policies in Indonesia still need to be strengthened. in 2019 there were around 15 million users of online loan services in Indonesia. In 2020 this number has increased by around 21 million users. In 2021 it is estimated that the number of users will increase again to 27 million. The results of this study indicate that consumer data protection and dispute resolution policies in Indonesia still need to be strengthened.